Curcumin Blocks High Glucose-Induced Podocyte Injury via RIPK3-Dependent Pathway - Chung, Hyunsoo; Lee, Seong-Woo; Hyun, Miri; Kim, So Young; Cho, Hyeon Gyu; Lee, Eun Soo; Kang, Jeong Suk; Chung, Choon Hee; Lee, Eun Young (Frontiers in Cell and Developmental Biology, 2022)
Podocyte loss is well known to play a critical role in the early progression of diabetic nephropathy. A growing number of studies are paying attention to necroptosis, a programmed form of cell necrosis as a mechanism of podocyte loss. Although necroptosis is a recently established concept, the significance of receptor interacting serine/threonine kinase 3 (RIPK3), a gene that encodes for the homonymous enzyme RIPK3 responsible for the progression of necroptosis, is well studied. Curcumin, a natural hydrophobic polyphenol compound responsible for the yellow color of Curcuma longa, has drawn attention due to its antioxidant and anti-inflammatory effects on cells prone to necroptosis. Nonetheless, effects of curcumin on high glucose-induced podocyte necroptosis have not been reported yet. Therefore, this study investigated RIPK3 expression in high glucose-treated podocytes to identify the involvement of necroptosis via the RIPK3 pathway and the effects of curcumin treatment on RIPK3-dependent podocytopathy in a hyperglycemic environment. The study discovered that increased reactive oxygen species (ROS) in renal podocytes induced by high glucose was improved after curcumin treatment. Curcumin treatment also significantly restored the upregulated levels of VEGF, TGF-β, and CCL2 mRNAs and the downregulated level of nephrin mRNA in cultured podocytes exposed to a high glucose environment. High glucose-induced changes in protein expression of TGF-β, nephrin, and CCL2 were considerably reverted to their original levels after curcumin treatment. Increased expression of RIPK3 in high glucose-stimulated podocytes was alleviated by curcumin treatment as well as N-acetyl cysteine (NAC, an antioxidant) or GSK′872 (a RIPK3 inhibitor). Consistent with this, the increased necroptosis-associated molecules, such as RIPK3, pRIPK3, and pMLKL, were also restored by curcumin in high glucose-treated mesangial cells. DCF-DA assay confirmed that such a result was attributed to the reduction of RIPK3 through the antioxidant effect of curcumin. Further observations of DCF-DA-sensitive intracellular ROS in NAC-treated and GSK′872-treated podocyte groups showed a reciprocal regulatory relationship between ROS and RIPK3. The treatment of curcumin and GSK′872 in podocytes incubated with high glucose protected from excessive intracellular superoxide anion production. Taken together, these results indicate that curcumin treatment can protect against high glucose-induced podocyte injuries by suppressing the abnormal expression of ROS and RIPK3. Thus, curcumin might be a potential therapeutic agent for diabetic nephropathy as an inhibitor of RIPK3.